Absence of pain in subjects with advanced radiographic knee osteoarthritis - Son, Kyeong Min; Hong, Jeong Im; Kim, Dong-Hyun; Jang, Dae-Gyu; Crema, Michel D.; Kim, Hyun Ah (BMC musculoskeletal disorders, 2020)
Background To investigate the frequency of pain among subjects with advanced radiographic knee osteoarthritis (OA) defined as Kellgren–Lawrence (KL) grade 4 and clinical features associated with pain. Methods Subjects from the Hallym Aging Study (HAS), the Korean National Health and Nutrition Examination Survey (KNHANES), and the Osteoarthritis Initiative (OAI) were included. Participants were asked knee-specific questions regarding the presence of knee pain. Clinical characteristics associated with the presence of pain were evaluated with multivariable logistic regression analysis. Results The study population consisted of 504, 10,152 and 4796 subjects from HAS, KNHANES, and OAI, respectively. KL grade 4 OA was identified in 9.3, 7.6, and 11.5% of subjects, while pain was absent in 23.5, 31.2, and 5.9% of subjects in KL grade 4 knee OA, respectively. After multivariable analysis, female gender showed a significant association with pain in the KNHANES group, while in the OAI group, younger age did. Advanced knee OA patients without pain did not differ from non-OA subjects in most items of SF-12 in both Korean and OAI subjects. Total WOMAC score was not significantly different between non-OA and advanced knee OA subjects without pain in the OAI. Conclusions Our study showed that a considerable number of subjects with KL grade 4 OA did not report pain. In patients whose pain arises from causes other than structural damage of the joint, therapeutic decision based on knee X-ray would lead to suboptimal result. In addition, treatment options focusing solely on cartilage engineering, should be viewed with caution.